CHRONICLE. (America Magazine: The Jesuit Review of Faith & Culture, 1913)
This section offers news briefs on world politics as of July 12, 1913. The Pennsylvania Legislature, reportedly enacted into law a bill designed to conserve the Pyatuning Swamp. The Fourth National Catholic Congress reportedly opened in Plymouth, England on July 1. The first military air-map has been published by the army authorities of Austria-Hungary.